2014
DOI: 10.1038/nature14059
|View full text |Cite
|
Sign up to set email alerts
|

Strong and deep Atlantic meridional overturning circulation during the last glacial cycle

Abstract: Extreme, abrupt Northern Hemisphere climate oscillations during the last glacial cycle (140,000 years ago to present) were modulated by changes in ocean circulation and atmospheric forcing. However, the variability of the Atlantic meridional overturning circulation (AMOC), which has a role in controlling heat transport from low to high latitudes and in ocean CO2 storage, is still poorly constrained beyond the Last Glacial Maximum. Here we show that a deep and vigorous overturning circulation mode has persisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
531
4
24

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(648 citation statements)
references
References 64 publications
62
531
4
24
Order By: Relevance
“…3d) point to a strong aridification and cooling in eastern Anatolia after 70 ka BP. The observation is consistent with low summer insolation (Berger, 1978;Berger et al, 2007), increased global ice volume (Shackleton, 1987), and cooler sea surface temperature (SST; Cacho et al, 2000), which, combined with the atmospheric effects of a weakening AMOC (Atlantic Meridional Overturning Circulation; Böhm et al, 2015;Bond et al, 1993) contributed to a widespread aridity across the Mediterranean region (e.g., Fletcher et al, 2010;Kwiecien et al, 2009;Sánchez Goñi et al, 2002).…”
Section: Abrupt Climate Changes During Mis 4-2supporting
confidence: 54%
“…3d) point to a strong aridification and cooling in eastern Anatolia after 70 ka BP. The observation is consistent with low summer insolation (Berger, 1978;Berger et al, 2007), increased global ice volume (Shackleton, 1987), and cooler sea surface temperature (SST; Cacho et al, 2000), which, combined with the atmospheric effects of a weakening AMOC (Atlantic Meridional Overturning Circulation; Böhm et al, 2015;Bond et al, 1993) contributed to a widespread aridity across the Mediterranean region (e.g., Fletcher et al, 2010;Kwiecien et al, 2009;Sánchez Goñi et al, 2002).…”
Section: Abrupt Climate Changes During Mis 4-2supporting
confidence: 54%
“…However, marine sediment core evidence suggests that the AMOC was temporarily weaker at this time (e.g. Böhm et al, 2015). Furthermore, this cooling persists at 125 ka when the data show an overall warming compared with the present day (see Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The contribution of the Greenland ice sheet to global LIG sea level rise has recently been quantified (Born and Nisancioglu, 2012;Colville et al, 2011;Helsen et al, 2013;NEEM community members, 2013;Quiquet et al, 2013;Stone et al, 2013), with the IPCC Fifth Assessment Report stating a range very likely between 1.4 and 4.3 m of equivalent sea level height . Taking contributions from thermal expansion and mountain glaciers into account and that global sea level was at least 6 m higher than today (Dutton et al, 2015), this implies that a contribution is likely also required from the WAIS (noted specifically by Colville et al, 2011) and/or other parts of the Antarctic ice sheet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is at variance with the prevailing view that there was little or no northern deep water present in the glacial North Atlantic (18,19), but a recent synthesis of Nd isotopes in the western Atlantic has also been interpreted as evidence for a glacial source of NADW (20). Furthermore, Böhm et al (21) found that some interstadials and the last interglacial on BR had lower eNd than in the modern ocean. This very low eNd could indicate there were both warm and cold climate processes that formed deep water in the North Atlantic that are inactive today.…”
mentioning
confidence: 69%